Bagaimana Dukungan Keluarga dan Kepribadian Wirausaha Memiliki Niat Berwirausaha - Nurmala Sari; Anggi Pratama; Novia Sri Dwijayanti (Universitas Batanghari Jambi, 2021)
This study aims to determine whether there is an influence between: (1) Family support on entrepreneurial intentions, (2) Entrepreneurial Personality on entrepreneurial intentions, (3) Family Support and Entrepreneurial Personality on Entrepreneurial Intentions. This research is a quantitative research with Ex-post facto method. Respondents in this study were 117 students from the Department of Social Science Education (PIPS). Testing the analysis using the analysis prerequisite test, regression assumption test and hypothesis testing. The data analysis technique used is multiple regression analysis. The results showed that: (1) there is an effect of family support on entrepreneurial intentions (2) there is an influence of entrepreneurial personality on entrepreneurial intentions (3) there is an effect of family support and entrepreneurial personality together on entrepreneurial intentions. The result of the coefficient of determination (R2) is 71.5%. It can be concluded that family support and entrepreneurial personality affect the entrepreneurial intentions of students of the Department of Social Sciences, Jambi University.